Epidural Analgesia for Severe Chest Trauma: An Analysis of Current Practice on the Efficacy and Safety - Jesse Peek; Reinier B. Beks; B. Feike Kingma; Marije Marsman; Jelle P. Ruurda; Roderick M. Houwert; Loek P. H. Leenen; Falco Hietbrink; Mirjam B. de Jong (Critical Care Research and Practice)
Background. Adequate pain control is essential in the treatment of patients with traumatic rib fractures. Although epidural analgesia is recommended in international guidelines, the use remains debatable and is not undisputed. The aim of this study was to describe the efficacy and safety of epidural analgesia in patients with multiple traumatic rib fractures. Methods. A retrospective cohort study was performed. Patients with ≥3 rib fractures following blunt chest trauma who received epidural analgesia between January 2015 and January 2018 were included. The main outcome parameters were the success rate of epidural analgesia and the incidence of medication-related side effects and catheter-related complications. Results. A total of 76 patients were included. Epidural analgesia was successful in a total of 45 patients (59%), including 22 patients without and in 23 patients with an additional analgesic intervention. In 14 patients (18%), epidural analgesia was terminated early without intervention due to insufficient sensory blockade (n=4), medication-related side effects (n=4), and catheter-related complications (n=6). In 17 patients (22%), the epidural catheter was removed after one or multiple additional interventions due to insufficient pain control. Minor epidural-related complications or side effects were encountered in 36 patients (47%). One patient had a major complication (opioid intoxication). Conclusion. Epidural analgesia was successful in 59% of patients; however, 30% needed additional analgesic interventions. As about half of the patients had epidural-related complications, it remains debatable whether epidural analgesia is a sufficient treatment modality in patients with multiple rib fractures.